FACTORS AFFECTING INDONESIAN YOUNG LEARNERS' ENGLISH PROFICIENCY LEVEL - Meisani, Diah Royani; Hamied, Fuad Abdul; Musthafa, Bahrudin; Purnawarman, Pupung (TEFLIN Journal, 2020)
This study was aimed at investigating the influencing factors on students' English proficiency levels based on Cambridge English Tests for Children and Young Learners. A preliminary survey was undertaken to select the sample of elementary schools that offered English as a subject. As many as 157 students who sat in Grades 4, 5, and 6 from nine elementary schools participated in this study. The findings revealed that the average of students' scores was at Starters/Movers Level, which is equal to A1 in the Common European Framework of Reference (CEFR). Through multiple regression analysis, three out of five investigated factors were detected to be significantly related to students' English proficiency levels, namely gender, grade level, and school accreditation rank. While rich literature has found gender and grade level as one of the affective variables in language learning, none has studied whether school accreditation status influences young learners' English achievement. It is recommended that schools and related stakeholders consider these factors to ensure effective English teaching to young learners. It is also suggested that future researchers conduct further study on how and under what conditions the factors can contribute to students' English achievement.